The Status of Infrastructure Services in East Asia and Pacific - World Bank Group (World Bank, Washington, DC, 2017)
Infrastructure plays an important role in the economic and social development of any country. Access to reliable, high-quality, efficient and affordable infrastructure services is a critical factor for reducing poverty and inequality, promoting economic growth and improving productivity, creating jobs, and promoting environmental sustainability and resilience in the face of major uncertainties including climate change. Given the World Bank Group’s active role in infrastructure development, the East Asia and Pacific (EAP) regional team has commissioned this report to take stock of the current levels of access, quality, tariffs, and costs associated with infrastructure services. This report aims to provide an overview of the status of economic infrastructure in several key sectors in the EAP region, particularly for networked infrastructure services such as urban water supply and sewerage, road transport, and electricity distribution. The exercise aims to shed light on the areas of greatest need, as well as to identify which sectors and geographical areas most require focused investments. The report also offers an account of trends and current levels of private sector investment in EAP countries to help inform financing strategies and decisions.